Integration of Scientific Literacy and Technology in Designing Early Childhood Learning - Kurniah, Nina; Agustriana, Nesna; Sapri, Johanes (Indonesian Journal of Early Childhood Education Studies, 2023)
This research is motivated by the problems and difficulties experienced by kindergarten teachers in designing learning through developments and technology as the implementation of 21st-century learning policies. This research aims to improve kindergarten teachers' ability to design and implement quality learning to realize the nation's next generation in a future full of challenges. The method used is classroom action research, with the Eliot model carried out through four stages. The research subjects are postgraduate students and early childhood education teachers. The results of this study indicate an increase in the ability of teachers to design and implement learning by integrating technology and scientific Literacy. by the age and level of development of early childhood to realize fun, meaningful, and innovative learning that can help children to live an authentic life in a future full of challenges. In addition, scientific Literacy helps children to form patterns of thought and behavior and build character to care and be responsible for themselves, society, and the universe, as well as prepare themselves to deal with problems faced in modern society that are very dependent on technology. Scientific and technological Literacy functioned as a unitary ability to obtain, evaluate, and then obtain strategies to process information and use it systematically in their duties as professional teachers.